(3GdJPcQI HCMhGd GdehJi hCehQ GdBNQIs - (3CHh YHO Gddg eMeO Hf CMeO Hf CHj HcQ Hf aQM GdCfUGQj GdNRQLj GdCfOdSj GdbQWHj, GdbQWHj,J (B671 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYdi GdGYdi Gdehdi GdPi Ndb aCMji hMce Ydi Ndbg HGdehJ hGdafG s
(3BNQgG (B:s
(3hUdi Gddg Ydi SjOfG eMeO NGJe GdfHjjf q s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B217s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B390s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJUha hGdBOGH GdTQYjIs